Nebulized Gadolinium‐Based Nanoparticles: A Theranostic Approach for Lung Tumor Imaging and Radiosensitization. Issue 2 (8th September 2014) - Dufort, Sandrine; Bianchi, Andrea; Henry, Maxime; Lux, François; Le Duc, Géraldine; Josserand, Véronique; Louis, Cédric; Perriat, Pascal; Crémillieux, Yannick; Tillement, Olivier; Coll, Jean‐Luc
Abstract : Lung cancer is the most common and most fatal cancer worldwide. Thus, improving early diagnosis and therapy is necessary. Previously, gadolinium‐based ultra‐small rigid platforms (USRPs) were developed to serve as multimodal imaging probes and as radiosensitizing agents. In addition, it was demonstrated that USRPs can be detected in the lungs using ultrashort echo‐time magnetic resonance imaging (UTE‐MRI) and fluorescence imaging after intrapulmonary administration in healthy animals. The goal of the present study is to evaluate their theranostic properties in mice with bioluminescent orthotopic lung cancer, after intrapulmonary nebulization or conventional intravenous administration. It is found that lung tumors can be detected non‐invasively using fluorescence tomography or UTE‐MRI after nebulization of USRPs, and this is confirmed by histological analysis of the lung sections. The deposition of USRPs around the tumor nodules is sufficient to generate a radiosensitizing effect when the mice are subjected to a single dose of 10 Gy conventional radiation one day after inhalation (mean survival time of 112 days versus 77 days for irradiated mice without USRPs treatment). No apparent systemic toxicity or induction of inflammation is observed. These results demonstrate the theranostic properties of USRPs for the multimodal detection of lung tumors and improved radiotherapy after nebulization. Abstract : The direct administration of Gadolinium‐based theranostic nanoparticles (USRPs) into the airways of a mouse bearing orthotopic human lung tumors enables the deposition of USRPs around the tumor nodules, their multimodal detection (fluorescence and MRI) and, due to the USRPs' radiosensitizing properties, augments significantly the impact of radiotherapy and mice survival.